Integrated multi-omics analysis reveals clinical significance of hepatocyte nuclear factor-1β in tumor immune microenvironment, immunotherapy and prognostic prediction for colon adenocarcinoma - Fushan Gao; Wenlin Gong; Haihua He; Zhen Zhang; Hongcai Yang; Fei Shao; Yibo Gao; Jie He (Cancer Immunology, Immunotherapy)
Abstract Background Research has consistently highlighted the key role of hepatocyte nuclear factor 1β (HNF1B) in organ development and cancer, including its involvement in colon cancer via shifted-code mutations. However, the specific effects of HNF1B on cancer immunotherapy and the immune microenvironment are not fully understood. This study investigated the impact of HNF1B on colon cancer immunotherapy in depth. Methods We analyzed 1,374 colon adenocarcinoma samples from the TCGA and GEO datasets. Our approach involved bioinformatics to uncover how HNF1B influences immunotherapy and the immune microenvironment, with corroboration from external databases and experimental validation. Results HNF1B was expressed at low levels in colon adenocarcinoma and was linked to patient prognosis. CIBERSORT, TIME, and GSVA analyses revealed that HNF1B was associated with macrophage infiltration, immune checkpoints, and signaling pathways. Drug prediction suggested a negative relationship between HNF1B and EGFR-targeted therapies, implying potential resistance. Validation with external cohorts confirmed that patients with low HNF1B expression experienced less benefit from immunotherapy. Conclusion This study clarifies the role of HNF1B in the treatment of colon adenocarcinoma. This study provides a foundation for further in-depth mechanistic studies and proposes new directions for optimizing immunotherapy strategies for colon adenocarcinoma.